Are preterm birth and very low birth weight rates altered in the early COVID (2020) SARS-CoV-2 era? - Rodriguez, Kayla; Nudelman, Matthew J.; Jegatheesan, Priya; Huang, Angela; Devarajan, Kamakshi; Haas, Jessica E.; Cervantes, Rosemarie; Falbo, Kelle; Narasimhan, Sudha Rani; Cormier, Machelnil; Stewart, Mary Beth; Patel, Rupalee; et al. (Frontiers in Pediatrics, 2023)
Objective We evaluated the prevalence of preterm birth (PTB) and very low birth weight (VLBW) during Jan-Dec 2,020 (early COVID era) at 5 hospitals (2 in West Virginia, 3 in California) compared to Jan 2017–Dec 2019 (pre-COVID) inclusive of 2 regional perinatal centers (1 in Huntington, WV and 1 in San Jose, CA) and 3 community hospitals (1 each in Cabell, Los Angeles and Santa Clara counties). Design/methods We examined PTB and VLBW rates of live births at 5 US hospitals from Jan 2017–Dec 2020. We compared PTB and VLBW rates in 2020 to 2017–2019 using Poisson regression and rate ratio with a 95% confidence interval. We stratified live births by gestational age (GA) (<37, 33–36, and <33 weeks) and birth weight (≤1,500 g, >1,001 g to ≤1,500 g, ≤1,000 g). We examined PTB rates at 4 of the hospitals during Jan-Dec 2020 and compared them to the prior period of Jan 2017–Dec 2019 using Statistical Process Control (SPC) for quarterly data. Results We examined PTB and VLBW rates in 34,599 consecutive live births born Jan 2017–Dec 2019 to rates of 9,691 consecutive live births in 2020. There was no significant change in PTB (<37 weeks GA) rate, 10.6% in 2017–2019 vs. 11.0% in 2020 (p = 0.222). Additionally, there was no significant change when comparing VLBW rates in 2017–2019 to 2020, 1.4% in 2017–2019 vs. 1.5% in 2020 (p = 0.832). Conclusion We found no significant change in the rates of PTB or VLBW when combining the live birth data of 5 US hospitals in 3 different counties.